Persepsi Guru Tentang Sekolah Penggerak Terhadap Minat Menjadi Guru Penggerak - Solichah, Aas Siti; Mubarok, M. Naelul; Irawan, Radika (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This research is motivated by the high interest in becoming a teacher leader in Indonesia. This study aims to obtain a clearer picture of how much influence Teachers' Perceptions About School Leaders have on Interest in Becoming Teacher Leaders. By knowing these things, it is expected to provide solutions and strategies in increasing the interest of prospective teachers to become leaders who are able to make changes in education in Indonesia. This research is a quantitative correlational study. The subjects in this study included the principal and teachers of SMP Mumtaza Islamic School Tangerang Selatan. Data collection techniques used include interviews, questionnaires and documentation. While the object in this study is the perception of teachers about school leaders on the interest in becoming teacher leaders. The data analysis technique in this study is the "F" test. H0 is accepted if Fcount <Ftable or sig> 5%. Meanwhile, Ha is accepted if Fcount> Ftable and sig <5%. Based on the results of the data analysis obtained, there is a contribution value of F = 12.208 with a sig value = 0.003 <0.005. Thus, it is concluded that there is a positive and significant influence between the perceptions of teachers of SMP Mumtaza Islamic School about the driving school on the interest of teachers to act as driving teachers.